Adoption of green fertilizer technology among paddy farmers: A possible solution for Malaysian food security - Adnan, N. (Elsevier Ltd, 2017)
Fertilizer is one of the critical contributions that is being used in order to improve agricultural productivity. Whereas, using Green fertilizer technology (GFT) is a means of improving the environmental concerns. Paddy production using green fertilizer technology potentially allows for sustainable development and helps farmers to increase the yield in Malaysia. The application of GFT in the modern agricultural industry is highly needed for food security in many developing nations, including Malaysia. The Malaysian government focuses more on paddy over other different essential crops for the implication of GFT because paddy has always been considered as the main commodity and the staple food crops for the country. Whereas, Malaysia needs to be self-sufficient because the nation produces nearly 72 of the paddy whilst the rest needs to be imported from other countries. Paddy yield in Malaysia is still lower than those other commodities under comparable conditions. Therefore, the production cost is significantly higher which results in a low perception about the adoption decision of GFT. Paddy production in Malaysia using GFT potentially allows for sustainable development and helps farmers to increase the yield. The foremost role of paddy farmers is to deliver sufficient food supply to the country. However, paddy farmers have largely managed their business by using traditional methods of farming with an outcome that is near to halting the productivity and farming income. Whilst, the Malaysian government, extension services, and Malaysian Agricultural Research and Development Institute (MARDI) stimulate paddy farmers to use GFT, which increases productivity without damaging the environment. This particular research focuses on the conceptual framework grounded on the Theory of Planned Behaviour (TPB), Theory of Reasoned Action (TRA), and Expected Utility Theory (EUT) in order to study the adoption decision of GFT amongst the Malaysian paddy farmers. This conceptual framework elucidates the adoption decisions by means of a self-motivated process, presuming a composite interaction group of a variable which came from all these three different theories. The combination of the TPB, TRA, and EUT overcomes some limitations that ascend when just one theory is used to examine the adoption decision amongst paddy farmers in Malaysia. Overall, the outcome of this research will suggest a strategic extension plan for advocating the use of GFT amongst farmers and hence help them to develop sustainable agricultural practices. Adoption of GFT amongst paddy farmers gives a possible solution for the Malaysian Food Security. © 2017 Elsevier Ltd